Relapsing Leukemia Infiltrating the Heart. (November 2015) - De Lazzari, Manuel; Fedrigo, Marny; Perazzolo Marra, Martina; Calabrò, Federica; Tarantini, Giuseppe; D'Amore, Emanuele G.S.; Adami, Fausto; Thiene, Gaetano; Iliceto, Sabino; Angelini, Annalisa; Tona, Francesco
Abstract : Supplemental Digital Content is available in the text.